Alteration of brain structural organization after sepsis with Fatigue - a structural brain network analysis - Seidel, Gundula; Ritter, Alexander; Bähr, Florian; Hamzei, Farsin (Archives of Community Medicine and Public Health, 2021)
In our recent cross-sectional investigation, we found in sepsis survivors with persistent cognitive impairment a high number of patients who still suffer from Fatigue. This finding is of importance because Fatigue is highlighted as an associated long-term sequela after sepsis and therefore these patients require an appropriate rehabilitation therapy. The aim of this study was to verify whether sepsis survivors with both cognitive impairment and Fatigue show any alteration in brain structure. 19 survivors of severe sepsis (longer than 2 years post sepsis) with persistent cognitive deficits ascertained with a battery of neuropsychological tests with cognitive and motor Fatigue symptoms (according to two German Fatigue scales) were investigated with a high-resolution. T1 weighted image of the brain at a 3.0 Tesla MRI scanner. The Voxel-based morphometry (VBM) was performed using VBM8 toolbox. 19 age- and sex-matched healthy control subjects were also scanned with MRI. VBM analysis revealed significant gray matter volume reduction in sepsis survivors particularly in the lateral frontal operculum and anterior cingulate cortex. These regions are part of the cingulo-opercular network which maintains alertness. Gray matter volume loss of the orbitofrontal cortex is functionally associated with Fatigue. These findings emphasize that networks of structural brain organization can be altered with corresponding clinical symptoms and neuropsychological deficits after sepsis.